Copyright Dot Com: The Digital Millennium in Copyright - Diotalevi, Robert N. (Online Learning, 1999)
With advanced technology come new legal issues. The age of information has given rise to greater concerns about copyright legalities. As new interpretations emerge from Congress as well as the courts, these thorny matters will be at the forefront. Copyright law ultimately affects anyone interested in higher education. Today the Internet, once a research project, is our largest computer system. The Information Super Highway offers a variety of useful information as one navigates down its maze of URLs, browsers and hyperlinks. The latest Clinton Administration measure, The Digital Millennium Copyright Act, is a massive complexity of rules and regulations. It will probably serve as a challenge for copyright aficionados, service providers and all involved in the field for some time to come. This work attempts to address the above issues as well as to explore new concerns in copyright.